How changes in financial incentives affect the duration of unemployment - Rafael Lalive; Jan C. van Ours; Josef Zweimüller (Center for Economic Studies and ifo Institute (CESifo), 2004)
This paper studies how changes in the two key parameters of unemployment insurance – the benefit replacement rate (RR) and the potential duration of benefits (PBD) – affect the duration of unemployment. In 1989, the Austrian government made unemployment insurance more generous by changing, simultaneously, the maximum duration of regular unemployment benefits and the earnings replacement ratio. We find that increasing the replacement ratio has much weaker disincentive effects than increasing the maximum duration of benefits. We use these results to split up the total costs to unemployment insurance funds into costs due to changes in the unemployment insurance system and costs due to behavioral responses of unemployed workers. Results indicate that costs due to behavioural responses are substantial.
Keywords: J64; J65; C41; 330; maximum benefit duration; replacement rate; unemployment duration; unemployment insurance; policy change; Arbeitslosenversicherung; Reform; Arbeitslosigkeit; Dauer; Schätzung; Österreich